Non-Newtonian Eyring-Powell-Casson Nanofluid Flow via Porous Medium: Numerical Analysis - Hymavathi, D. (Communications in Mathematics and Applications, 2023)
Investigations have been conducted in this paper by considering the combined convective Eyring-Powell Casson nanofluid through porous media with thermal radiation and chemical reaction. The possible comparability transformations are used to present a flow problem in a non-linear system of ordinary differential equations with the assistance of Keller-Box method, known as implicit finite difference scheme, where the important conclusions have been drawn and discussed in the form of graphs and through the validation of the numerical outcomes for the various values of flow parameters like thermophoresis parameter, viscous dissipation, thermal radiation, porosity, Brownian motion parameter, and fluid parameters.